Export of microRNAs: A Bridge between Breast Carcinoma and Their Neighboring Cells - Jahagirdar, Devashree; Purohit, Shruti; Jain, Aayushi; Sharma, Nilesh Kumar (Frontiers in Oncology, 2016)
Breast cancer is a leading type of cancer among women in India as well as worldwide. According to the WHO 2015 report, it has been anticipated that there would be a two-fold rise in the death due to breast cancer among women. The heterogeneous property of breast carcinoma has been suggested to be linked with dedicated set of communication and signaling pathway with their surroundings, which culminate into progression and development of the cancer. Among the plethora of communication tools in the hand of breast carcinoma cells is the recently appreciated exocytosis of the tightly packed short non-coding RNA molecules, predominantly the microRNAs. The recent studies suggest that microRNAs may work as courier messengers to participate in endocrine and paracrine signaling to facilitate information transfer between breast carcinoma and their neighboring cells. Evidence suggests that breast tumor cells communicate via packaged microRNAs in the tumor released micro-vesicles which enrich the tumor microenvironment. There is a strong view that dissecting out the mechanistic and regulatory aspects of microRNA export and role may uncover many prospects for overcoming the signaling defects and thereby controlling aberrant cell division. The detection of circulating microRNAs associated with breast carcinoma can also be used as biomarkers for early diagnosis. This review article is an attempt to provide updated knowledge on implications of short RNAs and their transport in the breast cancer pathophysiology.